Line of duty. Series 3 [videorecording (DVD)] - Mays, Daniel; Compston, Martin; McClure, Vicky, 1983-; Hawes, Keeley, 1976- (Acorn, 2016)
The critically acclaimed drama returns for six more riveting episodes. In this season, DC Kate Fleming and DS Steve Arnott of AC-12 investigate the conduct of Sergeant Danny Waldron of the Armed Response Unit.